Technological Innovations in Lifelong Language Learning: How Ubiquitous Platforms Integrate Language Education into Daily Life - Iin Almeina loebis; Michael Gallagher; Niamh Byrne (International Journal of Language and Ubiquitous Learning, 2026)
Background. Lifelong language learning has become an essential component of personal and professional development in today’s fast-paced, interconnected world. Technological innovations, particularly ubiquitous learning platforms, offer a promising approach to integrating language education into daily life. These platforms enable learners to practice language skills anytime, anywhere, fostering continuous learning and engagement. Despite their growing popularity, research on how these technologies support lifelong language learning is limited. Purpose. This study aims to investigate how ubiquitous learning platforms facilitate lifelong language learning by integrating language education into learners' daily routines. The research explores the role of these technologies in promoting sustained language acquisition and enhancing language proficiency over time. Method. A mixed-methods approach was employed, including quantitative language proficiency tests and qualitative interviews with users of various language learning platforms. Data were collected from 300 participants across different age groups and cultural backgrounds who engaged with mobile apps, online platforms, and other digital tools for language learning. Results. The findings demonstrate significant improvements in language proficiency, especially in vocabulary acquisition and speaking skills, among users of ubiquitous platforms. Participants reported high levels of motivation and consistent engagement, noting that the integration of language learning into daily activities enhanced their learning experience. Conclusion. Ubiquitous learning platforms play a crucial role in promoting lifelong language learning by providing flexible, engaging, and personalized language education experiences. These platforms effectively integrate learning into daily life, supporting continuous language acquisition across diverse learner populations.